Kebijakan Preventif Konflik Melalui Pendidikan Perdamaian Di Kota Yogyakarta - Suryo Wibisono; Nikolaus Loy (Jurnal Studi Diplomasi dan Keamanan, 2016)
Conflict is common things that happen in human interactions. Many ways to do conflict resolution, it can be pre- or post-conflict. In Post Indonesia reformation era, we facing so many conflicts that had happened and involve so many entities. Yogyakarta City is a town which well-known as a city of tolerance, and also melting point of much entity in Indonesia. Yogyakarta City as an education city had a responsibility to create peace character in every single educational level. Yogyakarta City Government should have a policy to create peace character in every citizen. Peace mindset should breed by education, as a conflict resolution process.